URGENSI DPR RI DALAM FUNGSI PENGAWASAN ANGGARAN DI INDONESIA - Apriandani, Babby; Sumantri, Sumantri; Sofian, Sofian; Sitompul, Ahmad Ray Fadilah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The role of the DPR (People's Representative Council) is important in building this country. Law No. 8 of 2012 concerning the Election of DPR Members, in which there is an explanation that the seats in it are 560 seats, which means that only 560 people can be in that place. The term of office of each DPR member is 5 years and ends simultaneously where the new DPR member takes his/her oath as a new DPR member with guidance from the Constitutional Court at a plenary session. In a simple sense, supervision can be interpreted as "an activity to assure and guarantee that the work carried out is in accordance with the established plan". For this reason, supervision must measure what has been achieved, assess activities, take corrective actions and adjustments that are considered necessary. In the decision of the Minister of State Apparatus Empowerment Number 19 of 1996, it is stated that supervision is the entire process of the object and/or activity that has been carried out in accordance with applicable provisions. Supervision is often interpreted as or identical to an examination or audit so that supervision means an audit. One of the obstacles in budget supervision by the Indonesian House of Representatives is the lack of Government Transparency. Not all budget data can be easily accessed by the Indonesian House of Representatives, especially related to budget use in various ministries and institutions. Keywords: Supervision, Budget Abstrak: Peran DPR (Dewan Perwakilan Rakyat) menjadi penting perannya dalam membangun negeri ini.  Undang Undang No. 8 Tahun 2012 tentang Pemilu Anggota DPR, didalamnya terdapat penjelasan bahwa kursi yang ada didalamnya ialah sebanyak 560 bangku yang artinya hanya 560 orang yang dapat berada di tempat tersebut. Untuk masa jabatan dari setiap anggota DPR ialah 5 tahun dan berakhir secara bersamaan dimana anggota DPR yang baru mengucapkan janjinya sebagai anggota DPR yang baru dengan panduan dari Mahkamah Konstitusi pada sidang paripurna. Dalam pengertian yang sederhana pengawasan dapat diartikan sebagai “kegiatan untuk meyakinkan dan menjamin bahwa pekerjaan yang dilakukan sesuai dengan rencana yang telah ditetapkan”. Untuk itu pengawasan harus mengukur apa yang telah dicapai, menilai kegiatan, mengadakan tindakantindakan perbaikan dan penyesuaian yang dianggap perlu. Dalam keputusan Menteri Pendayagunaan Aparatur Negara Nomor 19 Tahun 1996 disebutkan, pengawasan adalah seluruh proses objek dan atau kegiatan tersebut telah dilaksanakan sesuai dengan ketetapan yang berlaku. Pengawasan sering diartikan sebagai atau identik dengan pemeriksaan atau audit sehingga pengawasan mempunyai arti audit. Salah satu kendala dalam pengawasan anggaran oleh DPR RI antara lain yaitu kurangnya Transparansi Pemerintah, Tidak semua data anggaran dapat diakses dengan mudah oleh DPR RI, terutama terkait dengan penggunaan anggaran di berbagai kementerian dan lembaga. Kata kunci: Pengawasan, Anggaran